Pemanfaatan Buah Lontar ( Borassus Flabellifer) Pada Olahan Puding Sebagai Pangan Fungsional Untuk Kesehatan Tubuh - Dewi, Betna; Tri Yanuarto (Bengkulu Institute, 2024)
Siwalan tree or commonly referred to as palm tree (Borassus flabellifer) is a type of palm (areca nut) that grows in Southeast Asia and South Asia. Palm fruit has many benefits, one of which is that it can be processed into a variety of foods. This encoding program aims to determine the benefits of palm fruit and the processing of palm fruit can be in making pudding. The type of service carried out is experimental descriptive education. The sample used in this study was palm fruit and the result was in the form of pudding then organoleptic test to 10-15 respondents. Based on the results of the research that has been done, it can be concluded that lontar fruit pudding is favored by the majority of corensponden bai k in terms of taste, aroma and color so that it can be used as a business opportunity for the community. Keywords. : Lontar Fruit, Pudding, Body Health